Routine CT evaluation of central vascular ligation in patients undergoing complete mesocolic excision for sigmoid colon cancer. (10th June 2021) - Vogelsang, Rasmus Peuliche; Gögenur, Mikail; Dencker, Ditte; Bjørn Bennedsen, Astrid Louise; Levin Pedersen, Dorte; Gögenur, Ismail
Abstract: Aim: Objective and reproducible quality measures of complete mesocolic excision (CME) for colon cancer are not currently available. This study aimed to measure the inferior mesenteric stump length following CME for sigmoid colon cancer and explore surgical, pathological and oncological outcomes in patients with a stump length of <10 mm vs. ≥10 mm. Method: This was a single‐centre, retrospective cohort study including patients undergoing minimally invasive surgery for sigmoid colon cancer between May 2013 and May 2015. Follow‐up CT scans were reviewed, and a vascular stump cut‐off of <10 mm for adequate central ligation of the inferior mesenteric artery was applied. Differences in perioperative, histopathological and oncological outcome parameters (overall, disease‐free and recurrence‐free survival) were explored between <10 mm vs. ≥10 mm groups. Results: A total of 127 patients (43% female) with a median age of 68 years were included. The median follow‐up time was 68 months. CT measurements showed good interrater agreement (90% absolute agreement) and reliability among raters (kappa = 0.77, 95% CI 0.53–1.00, p  < 0.001). A stump length ≥10 mm was associated with longer operating time (150 vs. 180 min, p  = 0.021), intramesocolic resection ( p  = 0.008), and a shorter distance from the bowel wall to vascular tie (120 vs. 102 mm, p  = 0.005). Conclusion: An arterial stump length ≥10 mm in sigmoid resection for colon cancer was associated with key clinical quality measures. Measurement of arterial stump length using routine follow‐up CT may serve as a quality indicator of vascular ligation in CME surgery.